Enhancing transient stability of power systems using a resistive superconducting fault current limiter - Alashqar, Mohamed; Yang, Conghuan; Xue, Ying; Liu, Zhaoxi; Zheng, Weiye; Zhang, Xiao-Ping (Frontiers in Energy Research, 2023)
The electricity demand keeps increasing with development and time, which leads to the need to install more generating units in the grid. Therefore, the fault current levels will rise above the limits of the electrical equipment, particularly when the electric grid becomes meshed and interconnected with neighboring networks. Consequently, the electrical equipment needs to be replaced or use a method that will decrease the fault current to be within the permissible boundaries. The existing solutions such as neutral impedance, current limiting reactor (CLR), and bus splitting have negative impacts on the electric grid. The superconducting fault current limiter (SFCL) appears to be a promising solution. In this paper, the resistive SFCL is proposed to enhance the stability of the interconnected power system. The two-area system is used as a case study for the interconnected power system. Also, the optimal value and locations of the resistive SFCL are analyzed. The results show that the system will remain stable without tuning the power system stabilizer (PSS).